2011
DOI: 10.1158/1078-0432.ccr-11-1227
|View full text |Cite
|
Sign up to set email alerts
|

CDKN2A/BAlterations Impair Prognosis in AdultBCR-ABL1–Positive Acute Lymphoblastic Leukemia Patients

Abstract: Purpose: The 9p21 locus, encoding three important tumor suppressors (p16/CDKN2A, p14/ARF, and p15/CDKN2B), is a major target of inactivation in the pathogenesis of many human tumors.Patients and Methods: To explore, at high resolution, the frequency and size of alterations affecting this locus in adult BCR-ABL1-positive acute lymphoblastic leukemia (ALL) and to investigate their prognostic value, 112 patients (101 de novo and 11 relapsed cases) were analyzed by genome-wide single-nucleotide polymorphism arrays… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 50 publications
5
47
2
Order By: Relevance
“…The prognostic significance for adult ALL is controversial. Iacobucci et al 13 reported that CDKN2A/B deletions had independent significance for lower disease-free survival in a series of 112 adult Ph-positive patients, but other authors did not show any prognostic impact. 27 No differences in outcomes were observed from a comparison of heterozygous and homozygous CDKN2A/B deletions, 12 and this suggests an important haplo-insufficiency effect 28 or concomitant inactivation of the remaining allele by epigenetic events.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The prognostic significance for adult ALL is controversial. Iacobucci et al 13 reported that CDKN2A/B deletions had independent significance for lower disease-free survival in a series of 112 adult Ph-positive patients, but other authors did not show any prognostic impact. 27 No differences in outcomes were observed from a comparison of heterozygous and homozygous CDKN2A/B deletions, 12 and this suggests an important haplo-insufficiency effect 28 or concomitant inactivation of the remaining allele by epigenetic events.…”
Section: Discussionmentioning
confidence: 94%
“…[9][10][11] The prognostic implications of CNAs have been less studied in adult ALL. [12][13][14][15] IKZF1 and CDKN2A/B deletions have been associated with lower disease-free survival in adults with Philadelphia chromosome (Ph)-positive ALL, 13,14 but results from large series of Ph-negative patients are scarce. 12,15 The current study analyzed the frequency and prognostic significance of CNAs in adolescents and adults with B-cell ALL enrolled in risk-adapted protocols of the Spanish Programa Español de Tratamientos en Hematolog ıa (PETHEMA) group.…”
Section: Introductionmentioning
confidence: 99%
“…The OS of patients with B-ALL, particularly those with Ph -ALL carrying ≥3 gene deletions was poor with an increased CIR. Adult Ph + ALL patients carrying CDKN2A/2B deletions also exhibited a poor disease-free survival (DFS) (16). The present study evaluated the 2-year OS and RFS in different groups of patients.…”
Section: Discussionmentioning
confidence: 98%
“…Alterations in the cell-cycle pathway have been described in multiple cancers (8)(9)(10)(11)(12) and are associated with poorer clinical outcome in some tumor types (13)(14)(15), including acute lymphoblastic leukemia (9), ovarian (10), colon cancer (12), and medulloblastoma (11).…”
Section: Introductionmentioning
confidence: 99%